2019
DOI: 10.5398/tasj.2019.42.2.167
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Vertical Integration Intensity on Broiler Farms Technical Efficiency: The Case of Contract Farming in West Sumatera

Abstract: Contractual arrangements of different types have increasingly found in West Sumatera not only in subsistence and commercial crops but particularly also in livestock sector. Contract farming in livestock agribusiness is generally defined as broiler farms under an agreement between farmers and a livestock inputs supplier. Within this broad definition, there are different variants of contracts depending on the formality and intensity of contractual arrangement. This study objective was to prove that the design of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 21 publications
0
6
0
1
Order By: Relevance
“…Similarly, modelling a zero-inflated count data that has over-dispersion problems with ZIP also produces coefficients that are consistent but inefficient [ 36 , 42 ]. Fameye [ 43 ] therefore, proposed the use of ZINB to account for the over-dispersion problem under such circumstances. Over-dispersion in count data models arises when the variance of the count dependent variable is larger than its mean [ 38 ].…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, modelling a zero-inflated count data that has over-dispersion problems with ZIP also produces coefficients that are consistent but inefficient [ 36 , 42 ]. Fameye [ 43 ] therefore, proposed the use of ZINB to account for the over-dispersion problem under such circumstances. Over-dispersion in count data models arises when the variance of the count dependent variable is larger than its mean [ 38 ].…”
Section: Methodsmentioning
confidence: 99%
“…This is in line with the research conducted by [14] which stated that the training will help staffs dealing with the risk. In addition, it is important for smallholder layer farms to obtain a formal contract with suppliers as [15] suggested that the farms under a formal contract experience a greater level of technical efficiency and show a greater performance compared to those who do not possess a formal contract. Furthermore, it is important for the farm to develop an SOP in their production management system.…”
Section: Pa11mentioning
confidence: 99%
“…Di samping itu, peternak kemitraan internal hanya menerima harga sesuai kesepakatan, tidak terpengaruh naik turun harga pasar (Sarwanto, 2004). Hasil ini didukung hasil kajian Harianto (2019) dan Firiani ( 2014) yang menyebutkan produsen berperan sebagai price taker, sehingga hanya dapat menerima keputusan harga yang ditetapkan pedagang.…”
Section: Analisis Integrasi Pasar Ayam Broiler Jawa Barat Dan Pasar Indonesiaunclassified